Rocker in Cultural Studies: interview discussed with Dr. Lawrence Grossberg (in Thai) - Sawangchot, Viriya (Asia Social Issues, 2013)
This interview discussed with Dr. Lawrence Grossberg, “A.K.A:DocRock”, a prominent cultural studies scholar who is a Professor of Communications Studies and Cultural Studies, on rock formation and youth culture and the evolution of youth culture as a main field of cultural studies which he has been studies for over 30 years. ร็อก (เกอร์)ในวัฒนธรรมศึกษา: บทสัมภาษณ์ “ดอกเตอร์ร็อก” ลอว์เรนซ์ กรอสเบิร์ก บทสัมภาษณ์นี้ต้องการ “สนทนา” กับ ลอร์เรนซ์ กรอสเบิร์ก นักวิชาการทางด้านวัฒนธรรมศึกษาคนสำคัญหรือที่รู้จักกันนามว่า ด็อกเตอร์ร็อก กรอสเบิร์ก เป็นผู้บุกเบิกการศึกษา ถึงปรากฏการณ์ของ “การก่อรูปของร็อก” และ วัฒนธรรมเยาวชนในแนวทางของวัฒนธรรม ศึกษา ซึ่งเขาเองได้ทำการศึกษาในเรื่องราวเหล่า นี้มามากกว่า 30 ปี